Asymptotic behavior of evolution systems in arbitrary Banach spaces using general almost periodic splittings - Kreulich Josef (Advances in Nonlinear Analysis, 2016)
We present sufficient conditions on the existence of solutions, with various specific almost periodicity properties, in the context of nonlinear, generally multivalued, non-autonomous initial value differential equations,